Reproductive and Developmental Nanotoxicity of Carbon Nanoparticles - Holmannova, Drahomira; Borsky, Pavel; Svadlakova, Tereza; Borska, Lenka; Fiala, Zdenek (Nanomaterials (Basel, Switzerland), 2022)
The presented review aims to summarize the knowledge regarding the reproductive and developmental toxicity of different types of carbon nanoparticles, such as graphene, graphene oxide, multi- and single-walled nanotubes, fullerenes, and nanodiamonds. Carbon nanoparticles have unique chemical and physical properties that make them an excellent material that can be applied in many fields of human activity, including industry, food processing, the pharmaceutical industry, or medicine. Although it has a high degree of biocompatibility, possible toxic effects on different tissue types must also be taken into account. Carbon nanoparticles are known to be toxic to the respiratory, cardiovascular, nervous, digestive system, etc., and, according to current studies, they also have a negative effect on reproduction and offspring development.
Keywords: graphene; carbon nanoparticles; reproduction; MWCNT; nanotoxicity